УТОЧНЕНИЙ МЕТОД РОЗРАХУНКІВ ПАРАМЕТРІВ ЕЛЕКТРОМАГНІТНИХ І ЕНЕРГЕТИЧНИХ ПРОЦЕСІВ В ЕЛЕКТРИЧНИХ КОЛАХ ЗІ СТАЛЛЮ В РЕЖИМІ НАСИЧЕННЯ - Загірняк, М.В.; Прус, В.В.; Мілявець, Д. (Інститут електродинаміки НАН України, Київ, 2015)
The reasons for increased degree of saturation of magnetic system of electric machines with a long error-free running time are substantiated. It is proved that application of the conventional methods of calculation of electromagnetic and power processes parameters at practical degrees of saturation results in inadmissible errors. During the process of the problem solution an improved parameter calculation method applicable under the considered conditions is grounded. A sufficient degree of coincidence of the calculation results with the experimental data as to integral parameters and instantaneous power and electromagnetic characteristics is obtained. References 8, table 1, figures 6.